The effects of mandatory private disclosure on public disclosure: Evidence from CbCR - Raphael Müller; Johannes Voget; Jan Zental (Schmalenbach Journal of Business Research (SBUR), 2024)
We analyze the effect of increased mandatory private disclosure to fiscal authorities on voluntary public disclosure decisions. We exploit the introduction of Country-by-Country Reporting (CbCR), which requires large multinational corporations to report detailed geographic segment information to fiscal authorities to prevent income shifting. Using both difference-in-differences and regression discontinuity designs in our empirical approach, we investigate how multinational corporations respond to CbCR in their public disclosure of geographic information in financial statements and the narrative part of annual reports. We find that firms subject to CbCR decrease their disclosure of qualitative and sensitive geographic information. This effect is particularly pronounced for firms potentially subject to higher scrutiny by tax authorities and for firms with a~stronger international presence. Our results suggest that private and public disclosure of geographic information are substitutes in the context of the mandatory private reporting requirement under CbCR.
Keywords: H26; M41; M48; 650; CbCR; Mandatory Private Disclosure; Tax Avoidance; Voluntary Public Disclosure